1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Finding max/min given contraint

  1. Dec 15, 2008 #1
    1. The problem statement, all variables and given/known data

    Find the product of the maximum and minimum values of the function f(x, y) = xy
    on the ellipse (x^2)(1/9) + y^2 = 2

    3. The attempt at a solution

    I tried soving using lagrange multiplier and got:

    fx = y - (2/9)(x*lambda)
    fy = x - 2y*lambda
    flambda = (x^2)(1/9) + y^2 - 2

    then I set these = 0, but my answer came out wrong.. any suggestions for figuring out the min/max?
    1. The problem statement, all variables and given/known data

    2. Relevant equations

    3. The attempt at a solution
  2. jcsd
  3. Dec 15, 2008 #2
    For y I'm getting, [tex] y = \pm 1 [/tex]

    The way I set this up was as follows:


    [tex] f(x,y) = xy; g(x,y) = \frac{x^{2}}{9} + y^{2} = 2 \Rightarrow h(x,y,\lambda) = f(x,y) + \lambda g(x,y) [/tex]

    (Note that the sign in front of [tex] \lambda [/tex] does not matter)

    So let's take our partials, we get:

    [tex] \frac{dh}{dx} = y + \frac{2 \lambda}{9}x, \frac{dh}{dy} = x + 2 \lambda y, \frac{dh}{d\lambda} = \frac{x^2}{9} +y^2 - 2 [/tex]

    We know that each of those partials vanish i.e. we can set each to 0.

    The first one gives us

    [tex] 9y = -2 \lambda x [/tex]

    and the second one gives us

    [tex] \frac{x}{y} = -2 \lambda[/tex]

    And by simple substitution we get:

    [tex] 9y^{2} = x^{2} [/tex]

    So let's substitute it into our 3rd equation to get:

    [tex] y^{2} + y^{2} = 2 [/tex]

    Which yields our desired result of [tex] y = \pm 1 [/tex]. Now we can plug this into our g(x,y) to get [tex] x = \pm 3 [/tex]

    Note that it doesn't matter which value for y we pick therefore our solution set will be:

    [tex] (1,3), (1,-3), (-1,3), (-1,-3) [/tex]

    Now if you don't want to do this using Lagrange Multipliers, we can just realize that we can rewrite our g(x,y) as

    [tex] y = \pm \sqrt{2 - \frac{x^2}{9}} [/tex]

    and now we can substitute this into our f(x,y) get an equation of one variable i.e.

    [tex] \bar{f}(x) = \pm x \cdot \sqrt{2 - \frac{x^2}{9}} [/tex]

    Now we can proceed using the techniques you learned in Calculus 1 (I'm going to use Maple because I'm lazy)

    > a:=x*sqrt(2-x^2/9);

    a := [tex] \frac{1}{3} x \sqrt{18 - x}[/tex]

    > solve(diff(a,x)=0,x);

    -3, 3

    Note that choosing the negative root produces the same results.
    Last edited: Dec 15, 2008
  4. Dec 15, 2008 #3
    what equations are you using to get y = to +/- 1?
  5. Dec 15, 2008 #4
    Refresh your page :)
  6. Dec 15, 2008 #5
    Thanks!!! This helps a lot
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook